DESCRIPTION OF PRESDISPOSING FACTORS FOR WASTE MANAGEMENT BEHAVIOR IN SANGGAR BIMBINGAN HULU LANGAT, MALAYSIA 2023 - Khilda Nur Hurriyah; Ernyasih (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
The waste problem has developed into a serious problem that affects society as a whole, especially in urban areas, in many countries due to population growth, and social and economic activities. As long as humans live on Earth, the amount of waste produced by humans will continue to increase. Garbage is one of the results of human activity, and the amount of waste increases along with population. (Hartono, 2008). This type of research is descriptive quantitative research with the design used being cross-sectional which emphasizes measuring/observing independent and dependent variable data only once at a time. This research was carried out by distributing questionnaires which were then filled in independently by the respondents. The respondents for this research were 35 students from Kindergarten to Grade 6 elementary school students at Sanggar Guidance Hulu Langat. The sample in this study was taken from the entire student population. Then the data was analyzed using univariate analysis. The results show that there are 74.3% of respondents aged ≥ 6 – 12 years, the majority of respondents are male, namely 21 (60%), as many as 77.1% of respondents have good knowledge about waste management, and the majority of respondents, namely 74.3%, already have positive attitudes towards waste management. Students with good knowledge were 77.1%, and the majority of respondents 74.3% had positive attitudes towards waste management. Suggestions for students.